Let
a
,
b
,
c
,
d
be non-zero real numbers such that the function
f
(
x
)
=
c
x
+
d
a
x
+
b
defined on
R
\
{
−
c
d
}
has the following properties:
1)
f
(
1
9
)
=
1
9
2)
f
(
9
7
)
=
9
7
3)
f
(
f
(
x
)
)
=
x
Suppose that there is a unique number α such that α = f ( x ) for any real number x . What is the value of α ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Correct me if I'm wrong but after you said a = 5 8 c , you could have concluded with c a = 5 8 and the answer is 5 8 since c a is the horizontal asymptote.
You're right, I just wonder if this (19 + 97)/2=58... Has anything to do with the solutions of this kind of problems.
From the first two conditions, we know that the equation f ( x ) = x has two distinct solutions. Rewriting the equation we get: f ( x ) = c x + d a x + b = x ⇔ c x 2 + ( d − a ) x − b = 0 This equation has two solutions only if c = 0 . Obsereve that if we denote a ′ = a / c , b ′ = b / c and d ′ = d / c we get x + d ′ a ′ x + b ′ = c x + d a x + b = f ( x ) , so we may assume that c = 1 .
Observe that the coefficients of the composition f ∘ f correspond to the coefficients of the matrix ( a 1 b d ) ⋅ ( a 1 b d ) = ( a 2 + b a + d b ( a + d ) d 2 + b ) So, for the last condition ( f ( f ( x ) ) = x ) to hold we need the last matrix to be diagonal. This implies that d = − a . We have f ( x ) = x − a a x + b Now we will use the first two conditions to find a , b : we know that 1 9 , 9 7 are the solutions of the equation x 2 − 2 a x − b = 0 (from the equation above, substituting c = 1 , d = − a ). So x 2 − 2 a x − b = ( x − 1 9 ) ( x − 9 7 ) = x 2 − 1 1 6 x + 1 8 4 3 So a = 5 8 , b = − 1 8 4 3 and f ( x ) = x − 5 8 5 8 x − 1 8 4 3 It is easy to check that the only value f ( x ) can never achieve is a / c = 5 8
Hmm... using matrix composition. Interesting.
Problem Loading...
Note Loading...
Set Loading...
The condition f ( f ( x ) ) = x tells us that the function is self-inverse , that is, f − 1 ( x ) = f ( x ) . Inverting f ( x ) = c x + d a x + b gives us f − 1 ( x ) = c x − a − d x + b . Matching coefficients in these rational functions gives us the condition a = − d .
The two fixed points of f ( x ) = c x − a a x + b , x = 19 and x = 97, leads to ( a ⋅ 1 9 ) + b = 1 9 [ ( c ⋅ 1 9 ) − a ] and ( a ⋅ 9 7 ) + b = 9 7 [ ( c ⋅ 9 7 ) − a ] , produces the system of equations 3 8 a = 1 9 2 c − b , 1 9 4 a = 9 7 2 c − b , from which we obtain the relations a = 5 8 c , b = − 1 8 4 3 c .
Thus, our self-inverse function is
f ( x ) = c x − 5 8 c 5 8 c x − 1 8 4 3 c = x − 5 8 5 8 x − 1 8 4 3 .
Since 1843 is not a multiple of 58, there is no further simplification of this rational function (this is important, a point raised in one of the recent set of multiple-choice questions involving rational functions of linear polynomials). We see that the "limit at infinity" of this function is 58 , so the range of f ( x ) does not include this value. It should be noted that the domain of the function also does not include 58, as is expected for a self-inverse function. (Such functions are symmetrical about the line y = x . )